Surgical findings during exploratory laparotomy are closely related to mortality in premature infants with necrotising enterocolitis. (5th January 2017) - Hansen, ML; Juhl, SM; Fonnest, G; Greisen, G
Abstract: Aim: This study investigated whether a correlation existed between surgical findings during the first laparotomy for necrotising enterocolitis (NEC) and death and, or, disease progression. Methods: We included infants admitted within one day of birth to our tertiary neonatal department at Rigshospitalet, Denmark, from 2006 to 2015, who underwent a laparotomy for acute NEC. They were classified according to the locality and extent of intestinal necrosis by a paediatric surgeon, based on the surgical findings. We correlated the surgical findings with postoperative outcomes, namely death and, or, progression of NEC. Results: The first laparotomy showed that 48 infants had NEC, including 21 who demonstrated postoperative progression. Of these, six died before undergoing another laparotomy and 14 of the 15 infants who underwent relaparotomy also died. There was a significant association between surgical findings and NEC‐related mortality (p = 0.03). The association between surgical findings and the progression of NEC was also significant (p < 0.0001). Conclusion: Surgical findings during laparotomy for NEC were strongly correlated with mortality, which was close to 100% after relaparotomy. Considering the discouraging outcome, further studies should focus on alternative surgical approaches, such as proximal diverting jejunostomy and the clip and drop technique for the treatment of severe NEC.